IMPLEMENTASI MODEL RELATING,EXPERIENCING,APPLYING,COOPERATING,TRANSFERING TERHADAP PENINGKATAN LITERASI SISWA SD - Jaka Nugraha (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
The low interest in reading students in Indonesia is also in line with the low interest in writing. Interest in reading and writing is actually a foundation for someone to be able to improve their literacy skills. Interest in reading and writing is actually a foundation for someone to be able to improve their literacy skills. The purpose of the study was to find out how the REACT model could be applied to improve the literacy of elementary school students. With this model, it can train students to develop literacy skills because in learning students are required to understand a concept based on the given problem relating it to the experience and prior knowledge of students. This research is a type of descriptive research using a qualitative approach. The subjects involved in this study were teachers and students of grade VI SD. Data collection in the study was carried out by interview, observation, and documentation methods. The data obtained in this study were then analyzed using qualitative descriptive analysis and focused on the stages of data reduction, presentation, and drawing conclusions. The results of the research analysis showed that the increase in student literacy showed a very good improvement with the REACT model by inviting students to read stories, create written works, analyze text content, describe analytical inferences on texts, criticize texts and present creatively. Where all these activities have been able to be followed well by students with the REACT approach, which is to directly relate students to meaningful learning experiences.